2013
DOI: 10.1089/thy.2012.0471
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Levels Within Reference Range Are Associated with Heart Rate, Cardiac Structure, and Function in Middle-Aged Men and Women

Abstract: Background: Triiodothyronine (T3) has many effects on the heart, and marked changes in cardiac function and structure occur in patients with (subclinical) thyroid disease. We investigated whether between-subject variation in thyroid hormone levels within the euthyroid range is also associated with heart rate and echocardiographic heart function and structure. Methods: Subjects were selected from the Asklepios study (n = 2524), a population-representative random sample of patients aged between 35 and 55 years, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
31
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 50 publications
6
31
0
1
Order By: Relevance
“…This suggests an individual set point for pituitary-thyroid axis function (1). We and others have shown that this between-subject variation in TH levels, although within the normal range, is nevertheless associated with a number of clinical parameters such as bone mass, BMI, metabolic indices, and heart rate (2,3,4,5). The physiological basis of the set point of this axis is poorly understood (6).…”
Section: Introductionmentioning
confidence: 97%
“…This suggests an individual set point for pituitary-thyroid axis function (1). We and others have shown that this between-subject variation in TH levels, although within the normal range, is nevertheless associated with a number of clinical parameters such as bone mass, BMI, metabolic indices, and heart rate (2,3,4,5). The physiological basis of the set point of this axis is poorly understood (6).…”
Section: Introductionmentioning
confidence: 97%
“…4-t-OP and other endocrine-disrupting compounds have been linked to endocrine disruption mediated via interference with the estrogen and thyroid hormone systems [27]. A strong positive correlation between levels of thyroid hormone and heart rate has been demonstrated [28]. Thus, based on those studies, we assume that 4-t-OP may reduce heart rate through its effects on reducing thyroid hormone.…”
Section: Discussionmentioning
confidence: 92%
“…Roef et al found that fT3 level was positively associated with the peak velocity of systolic mitral annulus and late ventricular filling, whereas negatively with left ventricular end-diastolic diameter. 8) It suggested that euthyroid subjects with low-normal fT3 levels had an increased risk to suffer relatively reduced heart function, decreased fT3 level within the low-normal range might be associated with the severity of cardiac insufficiency. On the other hand, CRT can improve fT3 levels after a reverse of cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] Recently, fT3 level was shown to be associated with cardiac function and heart structure in euthyroid subjects without HF. 8) In addition, another research reported hypothyroidism was associated with a worse prognosis after CRT implantation, but it did not supply values for complete thyroid panel (fT3 and fT4). 9) Is the prognosis of patients with HF after CRT implantation is correlated with lower fT3 levels within a normal reference range?…”
mentioning
confidence: 99%